Structural analysis of Red1 as a conserved scaffold of the RNA-targeting MTREC/PAXT complex - Anne-Emmanuelle Foucher; Leila Touat-Todeschini; Ariadna B. Juarez-Martinez; Auriane Rakitch; Hamida Laroussi; Claire Karczewski; Samira Acajjaoui; Montserrat Soler-López; Stephen Cusack; Cameron D. Mackereth; André Verdel; Jan Kadlec (Nature Communications, 2022)
Unwanted RNA transcripts are targeted for degradation by nuclear complexes such as MTREC/PAXT. Here, the authors structurally and functionally characterized three interfaces of the scaffold protein Red1, providing mechanistic insights into conserved features of MTREC/PAXT architecture.